1998
DOI: 10.1161/01.atv.18.8.1217
|View full text |Cite
|
Sign up to set email alerts
|

Potencies of Lipoproteins in Fasting and Postprandial Plasma to Accept Additional Cholesterol Molecules Released From Cell Membranes

Abstract: Abstract-To investigate the role of various lipoproteins in plasma to promote cholesterol efflux from cell membranes, potencies of lipoproteins in normolipidemic fasting and postprandial (PP) plasmas to accept additional cholesterol molecules from cell membranes were determined. We used red blood cells (RBCs) PϽ0.20). In fasting plasma containing a low level of VLDL and HDL, isolated chylomicrons supplemented to the plasma were Ϸ9ϫ more potent than HDL in boosting the capacity of plasma to promote cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 52 publications
3
18
1
Order By: Relevance
“…Postprandial lipemia observed in type IIB subjects was significantly associated with increase (ϩ23%; P Ͻ 0.005) at 2 h in the capacity of whole plasma to efflux cellular free cholesterol. This finding is consistent with a previous report (18) in which postprandial as compared with fasting plasma was more potent in promoting free cholesterol efflux from red blood cells; the mechanism of such efflux remains indeterminate however, but may primarily involve efflux of cholesterol by receptor-independent, passive diffusion. Earlier studies (13,34) have demonstrated that pre␤-HDL constitute preferential acceptors of cellular free cholesterol and thus increased levels of pre␤ HDL particles in plasma may enhance cholesterol efflux.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Postprandial lipemia observed in type IIB subjects was significantly associated with increase (ϩ23%; P Ͻ 0.005) at 2 h in the capacity of whole plasma to efflux cellular free cholesterol. This finding is consistent with a previous report (18) in which postprandial as compared with fasting plasma was more potent in promoting free cholesterol efflux from red blood cells; the mechanism of such efflux remains indeterminate however, but may primarily involve efflux of cholesterol by receptor-independent, passive diffusion. Earlier studies (13,34) have demonstrated that pre␤-HDL constitute preferential acceptors of cellular free cholesterol and thus increased levels of pre␤ HDL particles in plasma may enhance cholesterol efflux.…”
Section: Discussionsupporting
confidence: 93%
“…Such particles are a substrate for LCAT, and thus postprandial lipemia is characterized by activation of plasma LCAT activity (14)(15)(16)(17), a finding which led to the proposal that the postprandial phase is associated with activation of RCT (14). In earlier studies, the capacity of postprandial plasma lipoproteins from healthy normolipidemic subjects to promote receptor-independent cholesterol efflux from cell membranes was evaluated (18). Using red blood cells as donors of membrane cholesterol via passive diffusion in the aqueous phase, CMs were shown to represent the most potent acceptors of free cholesterol among postprandial lipoproteins.…”
mentioning
confidence: 99%
“…Reports such as these suggest that, in addition to serum cholesterol impacting the population kinetics of erythrocytes and platelets, erythrocytes may reciprocally impact serum cholesterol levels. In support of this postulate, in vitro studies indicate that human erythrocytes act as a reservoir of cholesterol for serum lipoproteins, presumably because of their high nonspecifi c cholesterol loading capacity ( 18,19 ).…”
Section: Discussionmentioning
confidence: 95%
“…In one in vitro study, it was indeed demonstrated that cholesterol efflux from red blood cells was highly correlated with LCAT and CETP activities in postprandial plasma as well as the concentration of secondary acceptors, such as chylomicrons, VLDL, and LDL, but not with the initial acceptor HDL. 43 However, in other in vitro studies, no association between CETP activity in plasma and cholesterol efflux from Fu5AH cells was observed. 44,45 A cholesterol efflux-enhancing role for CETP was also observed in human CETP transgenic mice but not in rabbits.…”
Section: Availability Of Cholesterol Acceptor Particlesmentioning
confidence: 85%